A Case Report Management of Bilateral Sudden Deafness - Yunita Wulandari; Jacky Munilson (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2022)
Introduction: Sudden deafness or sudden sensorineural hearing loss (SSNHL) is defined as sensorineural hearing loss of more than 30 dB at three consecutive frequencies within 3 days of onset, often unilateral, and only 0,4-3,4 % of patients with bilateral of sudden deafness. The definite cause of sudden deafness is only found in 10-15% cases and most of the cause was unkown (idiophatic). The management of systemic corticosteroid injection is the first choice in the treatment of SSNHL and can be combined with corticosteroid intratympanic injection. One case reported, A 33-year-old male patient with diagnosis of bilateral sudden deafness which is performed systemic corticosteroids and combined with dexamethasone injection intratympanic with the good result. Keywords: Sudden deafness, sensorineural hearing loss, intratympanic injection ABSTRAK Pendahuluan: Tuli mendadak didefinisikan sebagai kehilangan pendengaran sensorineural yang lebih dari 30 dB pada 3 frekuensi berturut-turut dalam onset 3 hari, sering unilateral, hanya sekitar 0,4-3,4% dari pasien yang mengalami tuli mendadak bilateral. Penyebab pasti tuli mendadak hanya ditemukan pada 10–15% kasus, sebagian besar penyebabnya tidak diketahui (idiopatik). Tatalaksana injeksi kortikosteroid sistemik menjadi pilihan utama pada tatalaksana tuli mendadak dan dapat dikombinasikan dengan kortikosteroid injeksi intratimpani. Dilaporkan satu kasus pasien laki-laki, 33 tahun yang didiagnosis dengan tuli mendadak bilateral yang dilakukan terapi kortikosteroid sistemik dan dikombinasikan dengan injeksi deksametason intratimpani dengan hasil yang baik. Kata Kunci: Tuli mendadak, tuli sensorineural, injeksi intratimpani